The Influence of Customers' Trust To Permission E-mail Marketing Acceptance And Purchase Intention of Online Paid Course - Salwa Qotrunnada; Aprilianty, Fitri (Integrasi Sains Media, 2024)
The world of education in Indonesia has developed along with technological advances and the use of the Internet, particularly during the pandemic, that make remote learning feasible. Alongside formal education, the demand for skill education has surged, creating an attractive market for online paid course players to penetrate, like MySkill. MySkill adopts various advertising strategies to promote its services, mainly email marketing. However, email marketing does not significantly influence customers' purchase intention of MySkill services. Therefore, this research intends to test the effect of customers' trust on permission email marketing and its subsequent influence on purchase intention. This research utilizes a quantitative approach by online survey and uses descriptive statistics and PLS-SEM to analyze the survey result. The results revealed that customers' trust significantly influences permission email marketing acceptance and purchase intention. Permission email marketing positively affects perceived usefulness and ease of use, increasing customer purchase intention. However, the relationship between perceived ease of use and purchase intention was not statistically significant. These findings are expected to give insight into developing better strategies for purchase intention in the educational technology industry or related industries.